Excellent liver retransplantation outcomes in hepatitis C‐infected recipients. (16th July 2013) - Kressel, A.; Therapondos, G.; Bohorquez, H.; Borg, B.; Bruce, D.; Carmody, I.; Cohen, A.; Girgrah, N.; Joshi, S.; Reichman, T.; Loss, G. E.
Abstract Survival outcomes for liver retransplantation (LRTx) after graft loss in HCV patients (HCV‐LRTx) are generally considered inferior to those after non‐HCV‐LRTx. Between January 1, 2005 and June 30, 2011, our center performed 663 LTx, including 116 (17.5%) LRTx, 41 (35.3%) of which were more than 90 d after the LTx. Twenty‐nine (70.7%) LRTx were performed in HCV antibody–positive individuals. We compared patient demographics, baseline characteristics and outcomes of our HCV‐LRTx group with the HCV‐LRTx patients from the most recent OPTN database covering the same time period. Our Kaplan–Meier HCV‐LRTx one‐, three‐, and five‐yr HCV‐LRTx patient survival rates were 86.2%, 79.0%, and 72.4%, respectively compared with the OPTN one‐, three‐, and five‐yr HCV‐LRTx survival rates of 73.3%, 59.0%, and 51.3% respectively. Likewise, our graft survival rates were higher than OPTN rates at all time points studied. We performed a higher percentage of HCV‐LRTx as simultaneous liver/kidney transplants (SLK) (37.9% vs. 21.8%) and recorded shorter warm (30 ± 4 vs. 45 ± 23 min) and cold ischemic times (5:44 ± 1:53 vs. 7:36 ± 3:12 h:min). Conclusion: In our experience, HCV‐LRTx patient and graft survival rates are comparable to LTx survival rates and are higher than the rates described by OPTN.